2014
DOI: 10.1016/j.mvr.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Objective area measurement technique for choroidal neovascularization from fluorescein angiography

Abstract: The purpose of this study was to develop a non-biased method of quantitatively measuring choroidal neovascularization (CNV) areas based on late-phase fluorescein angiography (FA) images. Experimental CNV was induced in Long Evans rats by laser disruption of the Bruch’s membrane. FA was performed weekly for 5 weeks. Multi-Otsu thresholding (MOT) was used to quantify CNV in late-phase FA images from both experimental rodent CNV and wet age-related macular degeneration patients (wAMD). Images were automatically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The peak of activation was detected at D4 after laser treatment which decreased at D7 and was sustained at D14. Astonishingly, the majority of activated cells was found in the inner retina whereas the laser scar is located at the outer retina (Guthrie et al, 2014). Most of the cells counted at D1 were found surrounding the scar.…”
Section: Discussionmentioning
confidence: 95%
“…The peak of activation was detected at D4 after laser treatment which decreased at D7 and was sustained at D14. Astonishingly, the majority of activated cells was found in the inner retina whereas the laser scar is located at the outer retina (Guthrie et al, 2014). Most of the cells counted at D1 were found surrounding the scar.…”
Section: Discussionmentioning
confidence: 95%
“…Although, each of the three methods assess slightly different aspects of CNV, all of them showed a clear effect caused by Nrp1 depletion. Postmortem histological analysis has the advantage that vascular elements and invading inflammatory cells can be identified separately and volume measurement of the CNV lesions can be obtained with high precision using confocal microscopy [38]. However, dissection and fixation artefacts might introduce noise into those volume measurements.…”
Section: Discussionmentioning
confidence: 99%
“… 44 In the present study, the increase in fluorescence area and intensity was used as an index for vascular leakage based on the grading system described previously. 31 We found that 52% of all laser-induced CNV lesions showed significant elevation of fluorescein signal (grade 3) in the eyes treated with STC-1 compared with 25% in the control eyes ( Fig. 2 ).…”
Section: Discussionmentioning
confidence: 71%
“…Late-phase images were chosen for analysis of fluorescein leakage to correspond with the clearance time of fluorescein from the vasculature and to avoid interference with the observation of hyperfluorescence from CNV. 31 FFA was graded by two masked investigators. When the two grades for a lesion did not match, the two investigators discussed the lesion grades and agreed on the final grade together.…”
Section: Methodsmentioning
confidence: 99%